2014
DOI: 10.1038/jp.2014.148
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mid-forehead and axillary temperatures in newborn intensive care

Abstract: MFH thermometry is not able to replace DAT temperature recording in the newborn intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
1
8
3
Order By: Relevance
“…This research hypothesized that the two measurement methods do not provide the same results; however, their differences need to be analyzed in depth to avoid errors in the clinical management of pediatric patients. The results of our data showed that a 0.41°C statistically significant mean difference exists between the two methods, ranging between −1.80 and +2.40, and these results are similar to those of other studies (Can et al, 2010;Robertson-Smith et al, 2015;Sethi et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…This research hypothesized that the two measurement methods do not provide the same results; however, their differences need to be analyzed in depth to avoid errors in the clinical management of pediatric patients. The results of our data showed that a 0.41°C statistically significant mean difference exists between the two methods, ranging between −1.80 and +2.40, and these results are similar to those of other studies (Can et al, 2010;Robertson-Smith et al, 2015;Sethi et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the reports of Sollai [1], Chiappini [12] and De Curtis [9] who also reported a good agreement between NTIT and mercury thermometers. This is however contrary to the findings of Sethi [2], Jarvis [7] and Robertson-Smith [8] who reported poor agreement between digital axillary and forehead infra-red thermometers. The reason for the disparity may be due to the fact these authors compared temperature readings using axillary digital thermometers and NTIT as opposed to axillary Mercury-in-glass thermometers used in this study; further stressing the fact that temperature measurement differed with the device used in measuring it [3].…”
Section: Discussioncontrasting
confidence: 85%
“…This connotes that the use of infra-red thermometer caused less disturbance or pain to the newborn during temperature measurement. Similarly, Robertson-Smith et al [8] and Sethi et al [2] reported a poor agreement between mid-forehead and digital axillary thermometry readings amongst newborns in an intensive care unit thus concluding that both methods of thermometry could not be used interchangeably in the newborn. Sollai et al [1] and De Curtis et al [9] on the other hand, reported a good agreement between Infra-red and axillary digital thermometry; and Infra-red and rectal mercury-in-glass thermometry respectively, in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…bladder, esophageal, and rectal) indicated that the peripheral devices showed poor accuracy when used to estimate core BT and inadequate sensitivity when used for fever detection in adults and children 8,9,22 . However, using a different research methodology, other authors, comparing the peripheral electronic devices, achieved contradictory evidence [32][33][34][35] . For example, some studies found that FHD IR thermometers could serve as a good alternative to AXL DGT due to their user-friendliness and speed of use 36 , while others, reporting great mean differences between the investigated devices, did not consider the FHD IR device as accurate as the AXL DGT thermometer 24,34,35 .…”
Section: Discussionmentioning
confidence: 99%